E-N-cadherin heterodimers define novel adherens junctions connecting endoderm-derived cells - Straub, Beate Katharina; Rickelt, Steffen; Zimbelmann, Ralf; Grund, Christine; Kuhn, Caecilia; Iken, Marcus; Ott, Michael; Schirmacher, Peter; Franke, Werner (The journal of cell biology, 2011)
Intercellular junctions play a pivotal role in tissue development and function and also in tumorigenesis. In epithelial cells, decrease or loss of E-cadherin, the hallmark molecule of adherens junctions (AJs), and increase of N-cadherin are widely thought to promote carcinoma progression and metastasis. In this paper, we show that this “cadherin switch” hypothesis does not hold for diverse endoderm-derived cells and cells of tumors derived from them. We show that the cadherins in a major portion of AJs in these cells can be chemically cross-linked in E-N heterodimers. We also show that cells possessing E-N heterodimer AJs can form semistable hemihomotypic AJs with purely N-cadherin-based AJs of mesenchymally derived cells, including stroma cells. We conclude that these heterodimers are the major AJ constituents of several endoderm-derived tissues and tumors and that the prevailing concept of antagonistic roles of these two cadherins in developmental and tumor biology has to be reconsidered.